Lower Body Dynamics for Rotational and Translational Activities: Cycling and Stair Climbing - Mihçin, Şenay; Karacaoğlu, Bilal (01. Izmir Institute of Technology, 2023)
Evaluation of human movement performance in activities of daily living is an important component in clinical and rehabilitation settings. Motion capture technology is an effective method for objective evaluation of human motion. Here, movement kinematics and kinetic data are obtained from healthy individuals. In this thesis, it is detailed the daily life movements based on stair climbing and cycling. The aim of this study is to examine the effects of human movement on the kinetic and kinematic variables of the hip joint during stair climbing and descending. Data were collected using the Qualisys motion capture system, force plates, ladder and bicycle. By analyzing data from different individuals here, great potential information can be gained for predicting the recovery and progression of movement for patients. In the future, the development of personalized therapy protocols in rehabilitation with individualized progression can be offered. Optimum design parameters for the individual device and exercise device can be obtained, and if the relevant joints are supported with implants, it is possible to obtain the necessary boundary conditions for personalized implant design and to collect the necessary data for implant design. The Results and Discussion Chapter illustrates and tabulates the calculated results. In the Findings and Discussion section of the thesis, the calculated results of the study are included. This section provides a comprehensive analysis of the data collected, highlighting the observed patterns, trends, and variations in hip joint kinematics and kinetics during selected activities. The Discussion section delves into the significance of the findings by comparing the findings with the available literature, identifying similarities and differences, and offering possible explanations for observed variations.

Günlük yaşam aktivitelerinde insan hareket performansının değerlendirilmesi, klinik ve rehabilitasyon ortamlarında önemli bir bileşendir. Hareket yakalama teknolojisi, insan hareketinin objektif olarak değerlendirilmesi için etkili bir yöntemdir. Burada hareket kinematiği ve kinetik veriler sağlıklı bireylerden elde edilir. Bu tezde, merdiven çıkma ve bisiklete binmeye dayalı günlük yaşam hareketlerini detaylandırılmaktadır. Bu çalışmanın amacı, merdiven çıkma ve bisilet sürme sırasında insan hareketinin kalça ekleminin kinetik ve kinematik değişkenleri üzerindeki etkilerini incelemektir. Veriler, Qualisys hareket yakalama sistemi, kuvvet plakaları, merdiven ve bisiklet kullanılarak toplanmıştır. Burada farklı bireylerden alınan verileri analiz ederek, hastalar için hareketin iyileşmesini ve ilerlemesini tahmin etmek için büyük potansiyel bilgiler elde edilebilir. Gelecekte, bireyselleştirilmiş ilerleme ile rehabilitasyonda kişiselleştirilmiş terapi protokollerinin geliştirilmesi önerilebilir. Bireysel cihaz ve egzersiz cihazı için optimum tasarım parametreleri elde edilebilir ve ilgili eklemler implantlarla desteklenirse, kişiye özel implant tasarımı için gerekli sınır koşullarının elde edilmesi ve implant tasarımı için gerekli verilerin toplanması mümkündür. Sonuçlar ve Tartışma Bölümü, hesaplanan sonuçları gösterir ve tablo haline getirir. Tezin sonuçlar ve tartışma bölümünde ise çalışmanın hesaplanan sonuçlarına yer verilmiştir. Bu bölüm, seçilen aktiviteler sırasında kalça eklemi kinematiği ve kinetiğinde gözlemlenen modelleri, eğilimleri ve varyasyonları vurgulayarak toplanan verilerin kapsamlı bir analizini sunar. Tartışma bölümü, bulguları mevcut literatürle karşılaştırarak, benzerlikleri ve farklılıkları belirleyerek ve gözlemlenen varyasyonlar için olası açıklamalar sunarak bulguların önemini araştırır.
Dönme ve öteleme aktiveleri için alt vücut dinamikleri: Bisiklet binme ve merdiven çıkma
Thesis (Master)--İzmir Institute of Technology, Mechanical Engineering, Izmir, 2023
Includes bibliographical references (leaves. 59-60)
Text in English; Abstract: Turkish and English
Keywords: Motion capture (MOCAP) systems; Kinematics; Daily life activities; Hip joint kinematics